3D chiral metamaterial modular design with highly-tunable tension-twisting properties. (March 2022) - Xu, Weiyun; Liu, Zhao; Wang, Liwei; Zhu, Ping
Abstract: Chiral mechanical metamaterials are featured by their strong chiral effect induced by the node rotation and ligament bending deformation of chiral geometries. Despite their good compression-twisting performance in single principal direction, existing 3D chiral metamaterial designs are restricted to isotropic mechanical properties due to the geometry constraints imposed on the parametric model. In this study, a modular design method of 3D chiral metamaterials is proposed. By dividing the unit cell into several independent design units, this method greatly increases the design freedom and makes it possible to tailor properties in three principal directions. An effective and efficient articulated multi-link mechanism model is developed to study the deformation mechanisms of the proposed metamaterial under both normal and shear loadings. Through both analytical micropolar homogenization and finite element simulations, we demonstrate that the proposed 3D chiral metamaterial exhibits highly tunable tension-twisting properties, which is not achievable with existing designs. With better adaptability and application prospects, it provides inspiration for the 3D chiral metamaterial design with special functionalities, such as energy-absorbing materials and dynamic cloaks. Graphical Abstract: ga1 Highlights: A novel 3D chiral metamaterial that enables modular design. The deformation mechanisms are studied under both normal and shear loadings. Highly tunable tension-twisting properties are demonstrated in both analytical and simulation results. Better chiral effects over benchmark materials for various size scaling factors.